Using a glucometer for home-based quantification of sugar in baked goods [Research note] - Fundador, Erwin Oliver V.; Calumba, Kriza Faye A. (2020)
Weight reduction can be achieved by reducing the amount of sugar in the diet. However, a lot of bakeries sell products without nutritional labels. This makes it difficult to implement a weight management plan that is based on the reduction of sugar. To solve this problem, a cheap analytical technique suitable for home use has to be developed. Commercial glucometers are enzyme-based electrochemical sensors used for monitoring blood glucose levels. These devices are easy to purchase, cheap (as low as USD 7.00 for the unit and USD 0.2 for the strip), portable, and can measure glucose levels in less than 10 seconds. In this paper, the suitability of a glucometer for determining sugar in baked goods was determined by comparing the results obtained with the use of HPLC-RID. The results obtained using both instruments were not significantly different (P < 0.05). Assuming the HPLC-RID values as the standard, the % error values for the measured amount of sugar per serving of egg cookies, graham crackers, and breadsticks were 0.41%, ?1.85%, and 6.02% respectively, which were all less than 10%. This study suggests that the glucometer used is a suitable instrument for home-based quantification of sugar in unlabeled baked goods.